ISLAM AND PUBLIC LEADERSHIP: AN ANALYSIS OF GENDER EQUALITY IN THE 2024 EAST JAVA REGIONAL HEAD ELECTION - Siti Mufarochah; M. Ganda Abdi Wibowo; Dini Amalia (EGALITA, 2025)
Abstract Women have the equal role to men, as demonstrated by their involvement in various professions such as education, healthcare, information technology, and political law. As Islam upholds the equality of men and women in spirituality, social responsibility, and intellect, women are not confined merely to domestic roles. They can actively contribute to public and political spheres when equipped with the necessary competence and commitment. The research problem addressed in this study is: what are societal perceptions regarding women serving as public leaders within the social and cultural context of East Java? The primary goal of this research is to investigate public views and islam on the role of women as public leaders in the context of 2024 East Java Regional Head Election, considering the prevailing social and cultural frameworks. This study applies a qualitative approach. The data collection involves three informants from diverse backgrounds: a community leader, a political activist, and a representative of a social community group. The results of this research reveal that the phenomenon of gender equality in regional leadership has affected more women to fearlessly advocate for gender equality. Moreover, women are expected to capably balance their professional careers with their familial responsibilities. Women support each other through women’s communities, religious organizations, and gender advocacy groups in order to to advocate for public policies related to various fields to achieve gender equality in addressing societal needs. Circles within islam and social community perspectives emphasize the need for women to enhance their skills to achieve parity in education and empowerment, despite the enduring strength of patriarchal norms in East Java.  Keywords: Gender Equality; Public Leadership; Regional Head Election.Abstrak Perempuan memiliki peran yang setara dengan laki-laki, sebagaimana terlihat dari keterlibatan mereka dalam berbagai profesi, termasuk pendidikan, kesehatan, teknologi informasi, serta hukum dan politik. Islam menegaskan kesetaraan laki-laki dan perempuan dalam aspek spiritualitas, tanggung jawab sosial, dan intelektualitas, sehingga perempuan tidak terbatas pada peran domestik semata. Perempuan dapat berkontribusi secara aktif dalam ranah publik dan politik sepanjang mereka memiliki kompetensi dan komitmen yang memadai.Permasalahan penelitian yang diangkat dalam studi ini adalah: bagaimana persepsi masyarakat terhadap perempuan yang berperan sebagai pemimpin publik dalam konteks sosial dan budaya Jawa Timur? Tujuan utama penelitian ini adalah untuk mengkaji pandangan masyarakat dan perspektif Islam mengenai peran perempuan sebagai pemimpin publik pada Pemilihan Kepala Daerah Jawa Timur 2024, dengan mempertimbangkan kerangka sosial dan budaya yang berkembang. Penelitian ini menggunakan pendekatan kualitatif. Pengumpulan data melibatkan tiga informan dengan latar belakang yang beragam: seorang tokoh masyarakat, seorang aktivis politik, dan seorang perwakilan komunitas sosial.Hasil penelitian menunjukkan bahwa fenomena kesetaraan gender dalam kepemimpinan daerah telah mendorong semakin banyak perempuan untuk berani memperjuangkan kesetaraan gender. Selain itu, perempuan diharapkan mampu menyeimbangkan karier profesional dan tanggung jawab keluarga. Perempuan saling memberikan dukungan melalui komunitas perempuan, organisasi keagamaan, dan kelompok advokasi gender untuk mendorong kebijakan publik di berbagai bidang guna mencapai kesetaraan gender dalam pemenuhan kebutuhan masyarakat.Pandangan dari kalangan Islam maupun komunitas sosial menekankan pentingnya peningkatan kapasitas perempuan agar mampu mencapai kesetaraan dalam pendidikan dan pemberdayaan, meskipun norma-norma patriarkal masih memiliki pengaruh yang kuat di Jawa Timur.  Kata Kunci: Kesetaraan Gender; Kepemimpinan Publik; Pemilihan Kepala Daerah